Faktor – Faktor Yang Berhubungan Dengan Kejadian Penyalahgunaan Narkoba Di Kecamatan Baturaja Timur Tahun 2022 - Deli Lilia; Sabtian Sarwoko; Fera Novitry (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2023)
According to data from the Ogan Komering Ulu Regency, the perpetrators of narcotics crimes committed in 2019 there were 75 cases of which 86% were grouped in the productive age of 18-40 years, in 2020 there were 82 cases and 90% were grouped in the productive age of 18-40 years, and In 2021 in the jurisdiction of the Ogan Komering Ulu Police, there were 95 cases of which 96% were grouped in the productive age of 18-40 years of narcotics abuse. The research design used is a quantitative research design with a case-control research approach. The population is all residents in East Baturaja sub-district, East Baturaja Police has 105,076 residents aged 18-40 years totaling 58 cases. The sample in this study is Cases are productive age 18-40 years who are really drug users as many as 58 people. While the controls are productive age 18-40 years who really do not use drugs as many as 58 people.It is known that the proportion of respondents who have bad social relationships and become drug abusers is 70.7% greater than the proportion of respondents who have good social relationships and become drug abusers as much as 12.2%. It is known that the proportion of respondents with heavy workloads becomes drug abuse as much as 67.7%, which is greater than the proportion of respondents with light workloads who become drug abusers as much as 22.2%. It is known that the proportion of respondents with severe stress who become drug abusers is 66.2% greater than the proportion of respondents with moderate stress who become drug abusers as much as 17.9%.The results of the chi square test get p value 0.000 < (0.5) which means there is a relationship between environmental association and drug abuse. The results of the chi square test get p value 0.000 < (0.5) which means there is a relationship between workload and abuse drugs. The results of the chi square test obtained p value 0.000 < (0.5) which means that there is a relationship between stress and drug abuse.